1993
DOI: 10.1172/jci116445
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 synthesis in the human hepatoma cell line Hep G2. Metformin inhibits the stimulating effect of insulin.

Abstract: High plasma plasminogen activator inhibitor-i (PAI-1) activity is associated with insulin resistance and is correlated with hyperinsulinemia. The cellular origin of plasma PAI-1 in insulin resistance is not known. The hepatoma cell line Hep G2 has been shown to synthesize PAI-1 in response to insulin. The aim of this study was to analyze the insulin-mediated response of PAI-1 and lipid synthesis in Hep G2 cells after producing an insulin-resistant state by decreasing insulin receptor numbers. The effect of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 62 publications
4
26
1
1
Order By: Relevance
“…23,24 Then, the fact that circadian variations in plasma PAI-1 were not considered for blood sampling and the particular composition of the population studied could both contribute to the lack of correlation observed between PAI-1, insulinemia, and BMI. Furthermore, despite demonstration of an in vitro effect of insulin on PAI-1 production by some cultured cells, [25][26][27][28][29] our results do not favor the hypothesis of a direct contribution of insulin to PAI-1 level regulation. They also underline the link between PAI-1 expression and a qualitative rather than a quantitative aspect of adipose tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…23,24 Then, the fact that circadian variations in plasma PAI-1 were not considered for blood sampling and the particular composition of the population studied could both contribute to the lack of correlation observed between PAI-1, insulinemia, and BMI. Furthermore, despite demonstration of an in vitro effect of insulin on PAI-1 production by some cultured cells, [25][26][27][28][29] our results do not favor the hypothesis of a direct contribution of insulin to PAI-1 level regulation. They also underline the link between PAI-1 expression and a qualitative rather than a quantitative aspect of adipose tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…It has already been reported that hepatocytes produce PAI-1 (Anfosso et al 1993), and plasma PAI-1 levels are more strongly related to liver steatosis than to adipose tissue accumulation (Alessi et al 2003). Our results may indicate that even a low liver fat content stimulates hepatocytes to produce PAI-1, which may be involved in cardiovascular risk (Bastard et al 2000).…”
Section: Discussionsupporting
confidence: 57%
“…In hepatocytes, PAI-1 synthesis is increased by inducing insulin resistance (Anfossa et al 1993), a relationship which has also been noted in clinical studies Potter van Loon et al 1993). However, the interpretation of such clinical studies is made complex by the powerful interrelationships between various features of the insulin-resistance syndrome, any of which may explain the increased levels of PAI-1 in insulin resistance and in NIDDM.…”
Section: Mechanisms Of Association: Thrombogenesis and Impaired Fibrimentioning
confidence: 79%